The possibility of religious freedom early natural law and the Abrahamic faiths - Taliaferro, Karen ca. 20./21. Jh. (Cambridge Cambridge University Press, 2019)
Religious freedom is one of the most debated and controversial human rights in contemporary public discourse. At once a universally held human right and a flash point in the political sphere, religious freedom has resisted scholarly efforts to define its parameters. Taliaferro explores a different way of examining the tensions between the aims of religion and the needs of political communities, arguing that religious freedom is a uniquely difficult human right to uphold because it rests on two competing conceptions, human and divine. Drawing on classical natural law, Taliaferro expounds a new, practical theory of religious freedom for the modern world. By examining conceptions of law such as Sophocles' Antigone, Maimonides' Guide of the Perplexed, Ibn Rushd's Middle Commentary on Aristotle's Rhetoric, and Tertullian's writings, The Possibility of Religious Freedom explains how expanding our notion of law to incorporate such theories can mediate conflicts of human and divine law and provide a solid foundation for religious liberty in modernity's pluralism.
Keywords: Freedom Of Religion; Natural Law; Abrahamic Religions